2020
DOI: 10.1177/0333102420974356
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular contact plays no role in trigeminal neuralgia secondary to multiple sclerosis

Abstract: Introduction A demyelinating plaque and neurovascular contact with morphological changes have both been suggested to contribute to the etiology of trigeminal neuralgia secondary to multiple sclerosis (TN-MS). The aim of this study was to confirm or refute whether neurovascular contact with morphological changes is involved in the etiology of TN-MS. Methods We prospectively enrolled consecutive TN-MS patients from the Danish Headache Center. Clinical characteristics were collected systematically. MRI scans were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
1
25
1
Order By: Relevance
“…Indeed, in TN-MS the primary cause seems to be demyelination along the intra-pontine trigeminal afferents. Therefore, the authors concluded that microvascular decompression should generally not be offered to TN-MS patients [ 88 ].…”
Section: Headache and Multiple Sclerosismentioning
confidence: 99%
“…Indeed, in TN-MS the primary cause seems to be demyelination along the intra-pontine trigeminal afferents. Therefore, the authors concluded that microvascular decompression should generally not be offered to TN-MS patients [ 88 ].…”
Section: Headache and Multiple Sclerosismentioning
confidence: 99%
“…Truini [16] believes that a dual concurrent mechanism explains trigeminal neuralgia in patients with multiple sclerosis. But Noory [17] has different opinion on it, he believes that neurovascular contact plays no role in trigeminal neuralgia secondary to MS. Paulo [18] reported 33 cases of MVD in the treatment of TN-MS, and a follow-up of 53.5 months after surgery indicated that the pain relief rate was 67%. They believed that although MVD is not as effective as classic TN in the treatment of TN-MS, it can still be recommended Choose, and the more severe the preoperative pain, the worse the surgical effect.…”
Section: Discussionmentioning
confidence: 99%
“…al. (1) about the role of neurovascular conflict (NVC) in patients with trigeminal neuralgia (TN) and multiple sclerosis (MS). They included 54 patients for a MRI analysis and found no significant difference between symptomatic and asymptomatic TN side concerning the prevalence of a NVC, while a brainstem demyelinating plaque (BDP) was more frequent on the symptomatic TN side compared to the asymptomatic one.…”
mentioning
confidence: 99%